Editorial Introduction - Catherine F. Compton-Lilly (Networks: An Online Journal for Teacher Research, 2012)
The public eye in America continues to position teachers as contributing to the demise of American society. They are accused of not knowing their craft, not preparing students for the future, and not helping children to score high enough on endless rounds of tests. The articles presented in this journal challenge these discourses. They are authored by educators who claim their expertise and abilities. This is the power of teacher research and this newest edition of Networks is a wonderful testament to the teacher knowledge and craft.